Implementasi Sistem Reward untuk Meningkatkan Kinerja Karyawan Di PT. Rangros Plastik Kota Malang - Yuliana, Rachma; Hastutik, Sri; Rokhmawati, Dian (Manajemen & Bisnis Jurnal, 2023)
Abstract. Human Resource Management (HRM) is the science and art of managing the relationship and role of labor to achieve the effectiveness and efficiency of company goals, employees, and society as a whole. In a competitive business, companies realize the importance of encouraging employee enthusiasm to improve performance through a reward system. both financial and non-financial. This study aims to understand employee perceptions of the existing reward system and identify the types of rewards that most affect employee performance at PT Rangros Plastik Malang City. The research method used is descriptive qualitative method with data collection triangulation techniques in the form of sources, time, and interview and observation methods. The results showed that although PT Rangros Plastik has implemented various forms of rewards, such as weekly salary, Holiday Allowance (THR), recreational incentives, and recognition and appreciation, its effectiveness is still limited by the low quality of human resources and the perception of employees who still often differentiate the rewards received. The implementation of a fair and transparent reward system is proven to improve employee performance. However, to achieve optimal results, it is necessary to adjust the reward system that is more in line with the needs and expectations of employees. This study concludes that the implementation of an effective reward system can make a positive contribution to improving employee performance and achieving company goals